1997
DOI: 10.1073/pnas.94.17.8948
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of neurite outgrowth using an electrically conducting polymer

Abstract: Damage to peripheral nerves often cannot be repaired by the juxtaposition of the severed nerve ends. Surgeons have typically used autologous nerve grafts, which have several drawbacks including the need for multiple surgical procedures and loss of function at the donor site. As an alternative, the use of nerve guidance channels to bridge the gap between severed nerve ends is being explored. In this paper, the electrically conductive polymer-oxidized polypyrrole (PP)-has been evaluated for use as a substrate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
800
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 994 publications
(834 citation statements)
references
References 28 publications
17
800
1
4
Order By: Relevance
“…Many CPs have demonstrated negligible toxicity across a wide range of cell types and explants, including clonal neural cells [1,2,11,140], primary neuroblastomas [59], cardiomyocytes [141], glial cells [59] and spiral ganglion explants [20]. It has also been shown that CPs provide a more conducive environment for cell attachment and growth than bare metal electrodes [1,13], and that CPs loaded with neurotrophins can stimulate neurite growth of target cells [2,6,69].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Many CPs have demonstrated negligible toxicity across a wide range of cell types and explants, including clonal neural cells [1,2,11,140], primary neuroblastomas [59], cardiomyocytes [141], glial cells [59] and spiral ganglion explants [20]. It has also been shown that CPs provide a more conducive environment for cell attachment and growth than bare metal electrodes [1,13], and that CPs loaded with neurotrophins can stimulate neurite growth of target cells [2,6,69].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Polypyrrole and its derivatives are the most widely used conducting polymers in biomedical applications due to their biocompatibility and customizability [31][32][33][34][35][36]. Polypyrrole has been electrically deposited onto the electrode site of the neural recording arrays together with CDPGYIGSR, a peptide fragment from laminin [9,37], to improve the neuron-electrode connection in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used for bio-sensing [5][6][7], as electrodes for stimulation or recording [8,9], for controlling cell adhesion, proliferation [10][11][12] and stem-cell differentiation [13], for controlled drug release [14,15] and even to mechanically stimulate cells [16]. They can be fabricated electrochemically using various counter ions [17,18] and modified with a variety of biomolecules [5,6,19].…”
Section: Introductionmentioning
confidence: 99%